A Comparative Study of Two Passenger Transportation Systems between Two Bangladeshi Cities - Iqbal, K Shahriar; Shil, Samir K (Journal of Naval Architecture and Marine Engineering, 2009)
Using life cycle impact assessment, required freight rate and the customer service time, the ecological impact and the economic performance of bus and water transportation systems were evaluated and compared for the Dhaka - Narayanganj route in Bangladesh. Then the benefit of modal shifting of passengers from bus to water transport is shown. The results are shown as three different comparison indices. The water transportation showed clear superiority in environmental and economic aspects. Only the âservice quality' went to the favor of bus. Â Keywords: Inland water transport, transportation planning, environmental pollution, life cycle assessment, Â sustainable development, Kyoto Protocol. Â Â Â doi:10.3329/jname.v2i2.928 Â Journal of Naval Architecture and Marine Engineering 2(2005) 1-10